Genetics of bovine abomasal displacement. Issue 1 (April 2015) - Zerbin, Ina; Lehner, Stefanie; Distl, Ottmar
Highlights: Displaced abomasum has become a common inherited disease in first lactation Holsteins. There is no other disease in dairy cattle showing such a high heritability. Quantitative trait loci and associated genomic regions were identified for Holsteins. Pathways for deposition of calcium, insulin-dependent diabetes mellitus and synaptic transmission were significant. Genes with significant effects on left displacements of the abomasum are located in genomic regions under positive selection for dairy cattle. Abstract: Displacement of the abomasum (DA) is a common inherited condition in Holstein cows. This article reviews the genetics of DA including risk factors, genetic parameters and molecular genetic results. Breeds other than Holsteins affected by DA include Guernseys, Jerseys, Brown Swiss, Ayrshires and Simmental-Red Holsteins. In most DA cases, left displacements of the abomasum (LDA) are seen. Lactation incidence rates are higher for DA in first lactation Holsteins compared to later lactations. For Holstein cows, heritability estimates for DA are between 0.03 and 0.53. Genetic correlation estimates among DA and milk production traits range from positive to negative. Genome-wide significant genomic regions associated with LDA are located on bovine chromosomes (BTA) 1, 3, 11, 20 and 23. Motilin -associated single nucleotide polymorphisms on BTA23 exhibit a functional relationship with LDA. Pathways for deposition of calcium, insulin-dependent diabetes mellitus and synaptic transmission are significantly related to LDA in Holsteins. Deciphering the DA-associated genomic regions and genes may be an important step in the quest to understand the underlying disease-causing mechanisms and in unravelling mutations with a causal relationship to DA.